Diagnostic accuracy of three cone beam computed tomography systems and periapical radiography for detection of fenestration around dental implants - Amir Eskandarloo; Samira Saati; Mahbubeh Purabdolahi Ardakani; Mohamadreza Jamalpour; Naser Mohammad Gholi Mezerji; Vahid Akheshteh (Contemporary Clinical Dentistry, 2018)
Context: Early detection of peri-implant bone defects is highly important to prevent further bone loss and implant failure. Aims: This study aimed to assess the diagnostic accuracy of three cone-beam computed tomography (CBCT) systems and periapical radiography for detection of fenestration around dental implants. Methods: Thirty-one titanium implants were placed in the bovine ribs, in which peri-implant fenestration were simulated. Using a round fissure bur, fenestration defects were created in the apical-third region of implants. CBCT and PA radiographs were obtained before and after creating the defects. The results were analyzed using Chi-square test; kappa coefficient; Cochran's Q-test; McNemar's test; and sensitivity, specificity, positive predictive value, and negative predictive value; and receiver operating characteristic curve. Results: A significant agreement was noted between the two observers in the detection of defect-free samples in all imaging systems (P < 0.05). In detection of samples with defects, a significant agreement was observed between the two observers in use of Cranex three-dimensional and NewTom 3G systems (P < 0.05), but the agreement was not significant for detection of defects in use of Promax 3D (P > 0.05). The results showed no significant difference among the four imaging systems in detection of defect-free samples while the difference was significant among the four groups for detection of defects (P < 0.05). NewTom had the highest sensitivity (75.81%) and specificity (100%) for detection of fenestration. Conclusions: Within the limitations of CBCT systems different kVp used by different systems, artifacts and noises that influences image quality, difference in diagnostic value of different CBCT systems is due to the differences in type of detector and voxel size. In terms of the type of detector, our results showed that NewTom 3G, which has a higher (kVP) than other systems and the highest accuracy for detection of fenestration.